Historic Engagements with Occidental Cultures, Religions, Powers
XI, 315 p.
Keywords: This book explores centuries of power relations and imperial and civilizing rhetorics, overarching themes highlighted in these infrequently heard accounts by eastern travelers to the West. Considered in depth are evolutions in mental frameworks and practices that led to the emergence of anticolonial consciousness and strategies of protest.